2021
DOI: 10.1186/s12891-021-04200-0
|View full text |Cite
|
Sign up to set email alerts
|

Metacarpal shaft fixation: a biomechanical comparison of dorsal plating, lag screws, and headless compression screws

Abstract: Background Metacarpal shaft fractures are common and can be treated nonoperatively. Shortening, angulation, and rotational deformity are indications for surgical treatment. Various forms of treatment with advantages and disadvantages have been documented. The purpose of the study was to determine the stability of fracture fixation with intramedullary headless compression screws in two types of metacarpal shaft fractures and compare them to other common forms of rigid fixation: dorsal plating an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…45 Purported advantages of IMS are early mobilization and no pin-site or soft tissue morbidity. 47 49 50 Compared with plate fixation, IMS may also allow for a faster return to work or sports, with reduced risk of adverse events because of a rigid fixation. 49 While both clinical and biomechanical studies support the utilization of IMS for unstable metacarpal fractures, 46 47 48 49 50 51 more prospective clinical trials are needed to provide evidence for IMS over IMKW and to investigate the effect of tendon, capsule, and cartilage injury during screw insertion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 Purported advantages of IMS are early mobilization and no pin-site or soft tissue morbidity. 47 49 50 Compared with plate fixation, IMS may also allow for a faster return to work or sports, with reduced risk of adverse events because of a rigid fixation. 49 While both clinical and biomechanical studies support the utilization of IMS for unstable metacarpal fractures, 46 47 48 49 50 51 more prospective clinical trials are needed to provide evidence for IMS over IMKW and to investigate the effect of tendon, capsule, and cartilage injury during screw insertion.…”
Section: Discussionmentioning
confidence: 99%
“…2,[45][46][47][48] However, metacarpophalangeal joint stiffness and extension lag are the reported complications with IMS 45. Purported advantages of IMS are early mobilization and no pin-site or soft tissue morbidity 47,49,50. Compared with plate fixation, IMS may also allow for a faster return to work or sports, with reduced risk of adverse events because of a rigid fixation 49.…”
mentioning
confidence: 99%
“…Previous studies have adopted in vitro experiments for metacarpal fracture fixation, human cadaveric bones [ 22 ], animal bones [ 7 ], or artificial bones [ 8 , 12 – 14 ]. We employed artificial metacarpal bone because fresh human metacarpal bones were difficult to obtain and because some literature and the American Society for Testing and Materials had used artificial bones for experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The load to failure of the experiment was 72.31 N, which was much lower than that of double lag screw fixation in the present study (153.6 N). [ 22 ] compared the fixation strength of dorsal plating, lag screw fixation, and headless compression screw fixation and revealed that headless compression screw fixation offered the most satisfactory fixation. The maximum fracture force and stiffness of the double lag screw fixation were 234.1 N and 172.18 N/mm, respectively, which were much higher than our results (153.6 N and 57.0 N/mm, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, most hand surgeons do not consider K-wire fixation to be suitable for the treatment of oblique metacarpal fractures. Lag screw fixation is a less invasive surgical procedure and typically results in favorable outcomes [ 27 ]. However, the uncertain mechanical stability of fixing by using only lag screws and the precise surgical technique required to place lag screws are major concerns for surgeons [ 27 ].…”
Section: Discussionmentioning
confidence: 99%